2010
DOI: 10.1507/endocrj.k09e-206
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Influence of Subclinical Hypothyroidism on the Functional Outcomes in Stroke Patients

Abstract: Abstract. Subclinical hypothyroidism (SCH) is thought to have an influence on stroke outcomes. However, few reports demonstrate a favorable relationship between the two. We evaluated this association in acute ischemic stroke. From Jan 2005 to Jun 2008, 756 acute ischemic stroke patients were recruited within seven days of onset. The patients with overt hypothyroidism/hyperthyroidism or other medical conditions that may affect thyroid function were excluded. Thyroid stimulating hormone (TSH) and free thyroxine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
2
30
0
4
Order By: Relevance
“…Similarly, in another study, a greater proportion of patients in the subclinical hypothyroid group achieved a favorable outcome at 1 and 3 months [7] , whereas no significant difference in the proportion of patients with a good outcome at 1 year according to TSH levels was reported in the study by Alevizaki et al [8] . It is worth pointing out that no adjusted analyses were performed in these 2 studies, thus making it difficult to interpret the findings.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Similarly, in another study, a greater proportion of patients in the subclinical hypothyroid group achieved a favorable outcome at 1 and 3 months [7] , whereas no significant difference in the proportion of patients with a good outcome at 1 year according to TSH levels was reported in the study by Alevizaki et al [8] . It is worth pointing out that no adjusted analyses were performed in these 2 studies, thus making it difficult to interpret the findings.…”
Section: Discussionmentioning
confidence: 77%
“…Two studies reported higher NIHSS scores at admission in IS patients with low triiodothyronine (T3) hormone levels [5,6] . Three other studies considered subclinical hypothyroidism based on TSH levels [7][8][9] . Among these studies, 2 studies found no significant difference in initial NIHSS scores [7,9] , although in one of these a trend toward a lower mean NIHSS score was noted in patients with subclinical hypothyroidism [9] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations